RANCANG BANGUN SISTEM MONITORING IOT PADA PENGISIAN BATERAI SEALED LEAD ACID BERBASIS APLIKASI MOBILE UNTUK MENCEGAH OVERHEATING DAN OVERCHARGING - Rizal W.H. Siagian; Leonardus Guido Adi Wungo; Rodrick Benediktus Kainama; I Gusti Agung Putu Raka Agung; Made Sudarma (Jurnal SPEKTRUM, 2025)
Sealed Lead Acid (SLA) batteries are prone to damage caused by overcharging and overheating during the charging process. To address this issue, this study aims to design and develop an Internet of Things (IoT)-based monitoring system integrated with a mobile application to wirelessly monitor the charging of two SLA batteries, as well as prevent overheating and overcharging. The system employs the INA219 sensor to measure voltage and current, and the DS18B20 sensor to measure temperature. Current, temperature, and voltage data are transmitted to Firebase using an ESP32 microcontroller and displayed on an Android application called MySyM, developed with Android Studio. This research successfully realizes a functional, accurate, and effective IoT-based monitoring system to enhance the safety of SLA battery charging. The analysis of test results for the INA219 and DS18B20 sensors shows a Mean Absolute Error (MAE) of 0.24995 V for voltage and 2.1068 °C for temperature on the 12 V battery, as well as 0.1299 V for voltage and 1.3295 °C for temperature on the 6 V battery, demonstrating high measurement accuracy.